2016
DOI: 10.4238/gmr.15027700
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of stocking on the genetic diversity of Colossoma macropomum in central Amazon, Brazil

Abstract: ABSTRACT. Tambaqui (Colossoma macropomum) is the main fish species farmed on a commercial scale in northern Brazil. In view of the current scenario of Brazilian aquaculture, studies on the genetic improvement and reproductive management of captive tambaqui are crucial in identifying the genetic variability of broodstocks and devising management practices. Genetic diversity of three tambaqui broodstocks in western Amazon was evaluated using molecular markers. Fin samples were collected from 89 fish; 38 from Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…While the production of C. macropomum is expanding, there are increasing concerns with regard to the maintenance of the genetic diversity of the farmed stocks, inbreeding depression, the potential of the farm stocks for the development of programs of genetic improvement, and the risk of intraspecific hybridization with wild populations. These problems have been aggravated by the history of domestication, the lack of any systematic breeding management, and the potential for interaction with wild populations in the Amazon basin, which makes the genetic improvement of existing stocks ever more necessary (Aguiar et al., ; Lopes et al., ; Queiroz, Sousa, Silva, & Inoue, ; Santos, Santana, Sá Leitão, Paula‐Silva, & Almeida‐Val, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the production of C. macropomum is expanding, there are increasing concerns with regard to the maintenance of the genetic diversity of the farmed stocks, inbreeding depression, the potential of the farm stocks for the development of programs of genetic improvement, and the risk of intraspecific hybridization with wild populations. These problems have been aggravated by the history of domestication, the lack of any systematic breeding management, and the potential for interaction with wild populations in the Amazon basin, which makes the genetic improvement of existing stocks ever more necessary (Aguiar et al., ; Lopes et al., ; Queiroz, Sousa, Silva, & Inoue, ; Santos, Santana, Sá Leitão, Paula‐Silva, & Almeida‐Val, ).…”
Section: Introductionmentioning
confidence: 99%
“…This reflects a number of sampling problems, such as the regional focus of many studies, the use of markers with a poor resolution, and the inadequate or indirect sampling of the broodstocks through the analysis of the fry. In addition, the studies often overlook important aspects of the captive environment, such as reproductive patterns, the effective population size of the farmed stocks, the risks of inbreeding depression, the potential for genetic improvement based on the existing broodstock, the differences in comparison with natural populations, and the associated chances of hybridization with these populations (Aguiar et al., ; Calcagnotto & Toledo‐filho, ; Gomes et al., ; Jacometo et al., ; Lopera‐Barrero et al., ; Lopes et al., ; Queiroz et al., ; Ribeiro et al., ; Santos et al., ; dos Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total DNA and cDNA were used as templates for amplification. The DNA was extracted from tambaqui fin samples as described by de Queiroz et al (2016), and the cDNA was transcribed from total RNA isolated from the ovary. Cloning was performed in a pGEM-T Easy vector, and sequencing was performed in a 3500 Genetic Analyzer (Applied Byosystems ® ).…”
Section: Gene Cloning and Sequencingmentioning
confidence: 99%
“…P. Aguiar et al, 2013;2018;N.M. Lopera-Barrero et al, 2015;Queiroz, Souza, da Silva, & Inoue, 2016;Ribeiro et al, 2016;Fazzi-Gomes et al, 2017). M. C. F. Santos et al (2007) and Fazzi- Gomes et al (2017) found high genetic variability in natural populations when compared to cultivated stock and little genetic differentiation and high gene flow between populations, indicating that these natural populations form a large panmictic population in the tributary system of the Amazon River.…”
Section: Introductionmentioning
confidence: 99%